DECISION MAKING AND MANAGERIAL PERFORMANCE: ANALYSIS OF ORGANIZATIONAL INTERNAL CONTROL, WORK EXPERIENCE AND LEADERSHIP STYLE (LITERATURE REVIEW OF HUMAN RESOURCE MANAGEMENT) - Yona Sari, Selvi (Dinasti International Journal of Digital Business Management, 2022)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the Determination of Decision Making and Managerial Performance: Analysis of Organizational Internal Control, Work Experience and Leadership Style, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this research library are that: 1) The Effect of Organizational Internal Control on Decision Making; 2) The Influence of Work Experience on Decision Making; 3) Influence of Leadership Style on Decision Making; 4) The Effect of Organizational Internal Control on Managerial Performance; 5) The Effect of Work Experience on Managerial Performance; 6) The Influence of Leadership Style on Managerial Performance; and 7) Effect of Decision Making on Managerial Performance.